Comparative study of Igel with proseal LMA for ease of insertion and effect on hemodynamics in pediatric patients - Ashraf, Nashrah; Zargar, Owais-ul-umer; Albina, Ayat; Farooqi, Ayaz (International Journal of Research in Medical Sciences, 2022)
Background: Supraglottic airway devices offer several advantages over endotracheal tube with regards to ease of insertion, hemodynamic stability, decreased airway morbidity, reduced requirement of drugs and smoother emergence from anesthesia. Objective was to compare two supraglottic airway devices, Igel and proseal LMA, with respect to ease of insertion, number of insertion attempts, time taken for placement of device and hemodynamic changes. Methods: This prospective, randomized observational study was conducted in a tertiary care hospital in India after obtaining approval from the ethical committee of the institute. Sample size consisted of 80 patients who were randomized into two groups with each group having 40 patients. Results: In our study it was found that Igel was easier to insert in 95% of the patients as compared to proseal laryngeal mask airway, whose insertion was found easy in 77.5% of the patients. There was higher success rate in first attempt insertion for Igel as compared to proseal laryngeal mask airway. 95% of the patients had successful device insertion in single attempt in group Igel and 77.5% of the patients had successful device insertion in single attempt in proseal laryngeal mask airway group. Time taken to insert Igel was significantly less (15.2 seconds) as compared to proseal laryngeal mask airway (26.1 seconds). Conclusions: The ease of insertion of Igel is better as compared to insertion of proseal laryngeal mask airway. The success rate in first attempt insertion for Igel is higher as compared to proseal laryngeal mask airway. Time taken to insert Igel was significantly less as compared to proseal laryngeal mask airway. However, there was no difference in hemodynamic parameters and oxygen saturation between the two groups.